The new China-Africa-Russia geopolitical order, towards a new world order? - (:unkn) unknown (My University, 2023)
The analysis we propose here highlights the reconfiguration of world geopolitics in general, and the modeling of the African geopolitical scene in particular, through a change in the balance of power and the interplay of players, symbolized by the strengthening of cooperation between the China-Russia-Africa trio. The changing situation can be seen in the opposition to the traditional version of world geopolitics marked by Western unilateralism, which is gradually crumbling to the detriment of multilateralism driven by emerging powers such as China and Russia. Are we really moving towards a new world order in which China and Russia, together with Africa, form a new decision-making center? What's in it for Africa?
Keywords: African Research